Genetic diversity of the Mexican Lidia bovine breed and its divergence from the Spanish population. (29th December 2016) - Eusebi, P.G.; Cortés, O.; Dunner, S.; Cañón, J.
Summary: Lidia bovine breed exists since the XIV century in the Iberian Peninsula. These animals were initially produced for meat but some, showing an aggressive behaviour which difficulted their management, were used to participate in popular traditional and social events. A specialization of the breed giving rise to the original Lidia population is documented in Spain since mid‐XVIII century. Following the same tradition than in the Spanish population, Mexico used aggressive animals at the beginning of the XX century until two families of breeders started importing Lidia breed bovines from Spain with the aim of specializing their production. Each family (Llaguno and González) followed different breeding managements, and currently, most of the Lidia Mexican population derives from the Llaguno line. Although genetic structure and diversity of the Spanish population have been studied (using autosomal microsatellite markers, Y chromosome DNA markers and mitochondrial DNA sequences), the Mexican population is not analysed. The aim of the study was to assess both the genetic structure and diversity of the Mexican Lidia breed and its relationship with the original Spanish population using the same molecular tools. A total of 306 animals belonging to 20 breeders issued from both existing Mexican families were genotyped, and the genetic information was compared to the previously existing Spanish information. Slightly higher levels of genetic diversity in Mexican population were found when comparing to the Spanish population, and the variability among populations accounted for differences within them showing mean values of 0.18 and 0.12, respectively. Animals from the Mexican breeders, belonging to each of the two families, clustered together, and there was little evidence of admixture with the Spanish population. The analysis of Y chromosome diversity showed a high frequency of the H6 haplotype in the Mexican population, whereas this haplotype is rare in the Spanish, which is only found in the Miura (100%) and Casta Navarra (38%) lineages. Mitochondrial DNA revealed similar haplotypic pattern in both Spanish and Mexican populations, which is in accordance with most of the Mediterranean bovine breeds. In conclusion, as the Mexican Lidia population had initially a small number of founders and its current population has been reared isolated from their Spanish ancestors since a long time, these bottleneck effects and a combination of mixed cattle origin are the factors that might erase any trace of the Spanish origin of this population.